Preferences (Attitudes and Preferences of Vegetables) of School Children Reviewed from knowledge - Ronasari Mahaji Putri; Susmini Susmini; Neni Maemunah (Universitas STRADA Indonesia, 2020)
However, in reality there are not many children who want to consume vegetables and fruits. The low consumption of vegetables and fruit in school children is due to multifactor. This study aims to determine the relationship of knowledge with preference (attitudes and preferences of vegetables). The design of the observational study using a cross sectional design.The population in this study were all children found in Yayasan Eleos Sukodadi Village, Wagir Sub-District, Malang Regency, with 57 children, with total sampling. The instrument uses 3 questionnaires with a total of 34 questions. Analysis of data to determine the relationship between preference knowledge (preferences and attitudes) of vegetables and fruit using rank spearman test.The results of the study show that most school children have sufficient knowledge (63,2%) and half of the respondents have good preferences (50.9%). The statistical test showed that there was no relationship between knowledge and vegetable preferences in school children